Penentuan Tipe Akuifer Daerah Bulontala Kabupaten Bone Bolango Menggunakan Metode Geolistrik - Dai, Elan; Zainuri, Ahmad; Akase, Noviar (Journal of Applied Geoscience and Engineering, 2022)
Research area Geographically, the location is at 0áµ’31'0''N - 0áµ’31'30'' North Latitude 123áµ’8'0'' - 123áµ’8'30'' East Longitude with an area of ± 22.02 km. The research location is an andesite lava hill unit. because the type of rock found at that location is andesite igneous rock. The purpose of this study is to determine the type or type of aquifer. The method used is in the form of collecting surface and subsurface geological data. The method used is the geoelectric method with the Schlumberger configuration. The results of the research for geological mapping of the research location have morphology in the form of volcanic plains and hills with an altitude of 200 meters above sea level. The statigraphic sequence at the research site is sorted from easy to leader, old unit in the form of Andesite and easy unit in the form of alluvial. As for the geological structure that plays a role in the study, the dominant direction is from the north to the south.Groundwater at the research site follows the topography of the research location which flows from south to north where the water flows from upstream to downstream, from high to low elevation points. based on the results of geoelectric research and well water data collection that the aquifer at that location is shallow with alluvial material types, sand and andesite igneous rocks.The type of aquifer at the research site obtained from geoelectric research is a free aquifer type (not compressed) and only has 1 boundary layer, namely andesite igneous rock.